Thai College Students’ Attitudes Toward Physics: Results from a Cross-Sectional Descriptive Study and Instructional Implications - Pengsuwan, Parkpoom; Klunboot, Saengkrit (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2025)
Understanding students' attitudes toward physics is crucial for educators to gain insight into students’ beliefs about the subject and its learning. It is also fundamental to learning design. This study used the Colorado Learning Attitudes about Science Survey (CLASS), an instrument designed to assess beliefs educators consider essential for effective physics learning. The primary objective was to examine college students' attitudes toward physics in Thailand and to analyze these attitudes across academic programs and by gender. Employing a descriptive, cross-sectional survey design, the study collected data from 567 freshman students enrolled in a public autonomous university in Thailand, designated under the Global and Frontier Research category by the Ministry of Higher Education, Science, Research, and Innovation. The findings revealed that students scored relatively higher in the Sense-Making/Effort and Real-World Connection categories; however, scores for Applying Conceptual Understanding and Problem Solving remained comparatively lower. Furthermore, a statistically significant difference was observed between genders, with male students scoring significantly higher on attitude toward physics than female students, with a small-to-moderate effect size. These results highlight patterns in students’ attitudes that may inform instructional considerations in first-year general physics courses, particularly in supporting the application of physics concepts to solve problems and fostering engagement among female students.